Effects of experimental intracerebral ventricular injection of amyloid beta peptide (1-42) aggregates on daily rhythms of Aβ-degrading enzymes in the hippocampus: Relevance to Alzheimer's disease pathophysiology. Issue 3 (September 2019) - Castro, Andrea; Coria-Lucero, Cinthia; Anzulovich, Ana; Navigatore-Fonzo, Lorena
Highlights: NEP, IDE and ECE1 expression display daily rhythms in the rat hippocampus. BMAL1 and RORα protein levels vary rhythmically in this brain area. CAT and GPx levels display a daily variation. An injection of Aβ aggregates phase shifts daily NEP, IDE and clock protein rhythms. The Aβ group showed a phase shift in CAT and GPx rhythms. Abstract: One of the main pathological features in the Alzheimer disease (AD) is the presence of senile plaques, primarily composed of Aβ peptide aggregates, in cortex and hippocampus. AD late onset, which constitutes 90% of cases, could be mainly attributable to deficiencies in the clearance of the Aß peptide. Here we show that expression of Aβ-degrading enzymes varies on a daily basis in the hippocampus. Interestingly, an intracerebroventricular injection of Aβ aggregates modified temporal patterns of Aβ-degrading proteases, as well as clock proteins (BMAL1 and RORα) and antioxidant enzymes (CAT and GPx) daily rhythms. Our findings showed that the increase of Aβ leads to the alteration of the enzymes involved in the clearance, and, consequently, to an increase of oxidative stress and alteration of the cellular redox state, affecting the functioning of the endogenous clock and daily rhythms of BMAL1, RORα and their target genes, in this disease.